Sparse data inpainting for the recovery of Galactic-binary gravitational wave signals from gapped data. Issue 4 (18th November 2021) - Blelly, Aurore; Bobin, Jérôme; Moutarde, Hervé
ABSTRACT: The forthcoming space-based gravitational wave observatory LISA will open a new window for the measurement of Galactic binaries, which will deliver unprecedented information about these systems. However, the detection of Galactic binary gravitational wave signals is challenged by the presence of gaps in the data. Whether being planned or not, gapped data reduce our ability to detect faint signals and increase the risk of misdetection. Inspired by advances in signal processing, we introduce a non-parametric inpainting algorithm based on the sparse representation of the Galactic binary signal in the Fourier domain. In contrast to traditional inpainting approaches, noise statistics are known theoretically on ungapped measurements only. This calls for the joint recovery of both the ungapped noise and the Galactic binary signal. We thoroughly show that sparse inpainting yields an accurate estimation of the gravitational imprint of the Galactic binaries. Additionally, we highlight that the proposed algorithm produces a statistically consistent ungapped noise estimate. We further evaluate the performances of the proposed inpainting methods to recover the gravitational wave signal on a simple example involving verification Galactic binaries recently proposed in LISA data challenges.